Transforming Religious Authority: Islamic Epistemology in the Digital Age - Muhdi Ali; Farih, Awan; Sholahuddin Al Ayubi; Andi Rosa (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The rapid development of digital technology has brought substantial changes in the production, distribution, and validation of Islamic knowledge, triggering fundamental epistemological challenges regarding the authority and legitimacy of religious discourse in the social media era. This study critically analyzes how digitalization transforms traditional religious authority and reconstructs the epistemology of contemporary Islamic thought, focusing on shifting patterns of production, validation, and distribution of religious knowledge. Using a qualitative approach that integrates literature studies and Fairclough's Critical Discourse Analysis (CDA), this study analyzes academic literature and digital content to uncover the ideological dimensions and power relations behind epistemological shifts in online Islamic discourse. The results show that digitalization shifts knowledge production from an institutional-hierarchical framework to a more flexible, participatory, and algorithm-driven space, where validation now relies more on popularity metrics than scientific accuracy. This shift gives rise to epistemic populism that replaces scientific authority with performative influence, implicating a decline in methodological depth and the polarization of Islamic identity. This study concludes that digitalization acts as an agent of epistemological transformation that demands the development of a hybrid Islamic epistemology, which combines classical scientific values with digital participatory methods to maintain scientific integrity.